Therapeutic Outcomes Following Uterine Lavage, Levamisole, PGF2α and their Combinations in Subclinical Endometritic Buffaloes - Singh, N.; Singh, B.; Kumar, R. (The Indian Journal of Animal Reproduction, 2021)
This study examined the effect of different therapeutic protocols on macro-mineral  profile and reproductive performance of endometritic buffaloes. Endometritic  buffaloes were assigned in five treatment and one control groups viz. uterine lavage  (UL), Levamisole (LEV), PGF2α (PG), Uterine lavage+Levamisole (UL+LEV),  Uterine lavage+PGF2α (UL+PG) and control (no therapy) consisting of six buffaloes  in each group. The Subclinical endometritic buffaloes were diagnosed using White  side test. The screened buffaloes were subjected to different treatment regimen as  mentioned earlier. It was observed that the post-treatment calcium and phosphorus  level was significantly (P0.05) change  was recorded in control group. The clinical cure rate of endometritis was 33.33,  50.00, 66.67, 66.67, 83.33 and 83.33% in untreated control, UL, LEV, PG, UL+LEV  and UL+PG, respectively. The corresponding conception rates were 16.67, 33.33,  50.00, 50.00, 66.67 and 66.67% in in untreated control, UL, LEV, PG, UL+LEV and  UL+PG, respectively. The results inferred that, uterine lavage along with levamisole  or PGF2α can be used effectively to manage endometritic buffaloes.
Keywords: Buffalo; Cloprostenol; Endometritis; Levamisole; Uterine lavage